The Challenges of Studying in an International School - Hilda Novita (Universitas Bunda Mulia, 2017)
The National Education Regulation No. 78 Year 2009 that allows the establishment of international schools in Indonesia has given opportunity for Indonesian parents who wish to enter their children into schools with English as the medium language. Studying in English medium schools, however, poses certain challenges for the students and one of them is their academic achievement since they have to learn the school subjects in a language that they have not mastered. Nevertheless, King and Fogle (2006) and Colorado (2008) mentioned various ways parents can support their children who study in schools with the second language as the medium of instruction. The aim of this paper is to examine whether the supports from family mentioned by King and Fogle (2006) and Colorado (2008) are able to help the students perform academically in the schools with English as the medium of instruction. This study used questionnaires as the source of data with Grade 11 and 12 students of an international school as the subjects to find out whether their academic achievement in school correlates with the supports given to them. This paper will benefit those in bilingual education sectors and parents who wish to promote the use of English in their schools. This may inform them more on what it takes to make the students successful and what are required to help the students perform academically. Keywords: international schools, academic performance, supports from family